2009
DOI: 10.1308/rcsann.2009.91.8.716c
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Contamination from Cement Fragments During Revision Hip and Knee Arthroplasty

Abstract: Ann R Coll Surg Engl 2009; 91: 711-717 716Coren et al. 1 argue that human vision favours horizontal or vertical lines rather than oblique lines. Thus, rather than use the standard anterior-posterior projected image of the hip, we routinely rotate the intensifier image so that the guide wire appears to be passing in a vertical direction. By rotating the image (Fig. 1) in this way, it becomes significantly easier to visualise the projected direction of the guide wire and, in doing so, ensure its accurate final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…While there are no studies comparing the two types of implants directly, both have shown good mid-term functional outcomes. 13 14 15 16 All surgeries were performed using a tourniquet, through a minimally invasive medial parapatellar approach. Intra-articular injections were given intraoperatively and modified based on patient's underlying comorbidities.…”
Section: Methodsmentioning
confidence: 99%
“…While there are no studies comparing the two types of implants directly, both have shown good mid-term functional outcomes. 13 14 15 16 All surgeries were performed using a tourniquet, through a minimally invasive medial parapatellar approach. Intra-articular injections were given intraoperatively and modified based on patient's underlying comorbidities.…”
Section: Methodsmentioning
confidence: 99%